Teachers’ Perspective: Revolutionizing English Classroom Interaction with Technology Integration - Faricha Rizqi (Journal of Islamic Studies and Education, 2023)
The integration of technology into language teaching has emerged as a prominent alternative for facilitating the classroom interaction. Thus, this study aims to present the teachers’ perspective on the use of technology in the learning activity, especially in English classroom integrated with the online feedback. The data were collected from the interview and observation involving teachers inside and outside the classroom. The sample for this study consisted of teachers from Senior High School in Surakarta, Central Java Province. The results of the study indicated that the use of technology integrated with the online feedback promoted meaningful teaching and learning activity. The integration of technology-based learning and online feedback in English classroom was effective, but it should also be added with the offline one, especially in giving the feedback to the students. In addition, this study found that teachers are confronted with a problem of the connection or networking using the technology. The results suggest for the effective use of technology in the learning activity.